2011
DOI: 10.1021/ml200223s
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel Series of CRTH2 (DP2) Receptor Antagonists Devoid of Carboxylic Acids

Abstract: Antagonism of the CRTH2 receptor represents a very attractive target for a variety of allergic diseases. Most CRTH2 antagonists known to date possess a carboxylic acid moiety, which is essential for binding. However, potential acid metabolites O-acyl glucuronides might be linked to idiosynchratic toxicity in humans. In this communication, we describe a new series of compounds that lack the carboxylic acid moiety. Compounds with high affinity (K i < 10 nM) for the receptor have been identified. Subsequent optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…13 N-(3-Cyano-5-fluorophenyl)benzamide (3e). 25 Yellow solid (35 mg, 73%); mp 145−146 °C; R f = 0.44 (petroleum ether/ethyl acetate = 4:1); 1 H NMR (400 MHz, CDCl 3 ): δ = 8.37 (s, 1H), 7.93−7.82 (m, 3H), 7.70 (s, 1H), 7.61−7.54 (m, 1H), 7.47 (dd, J = 10.5, 4.7 Hz, 2H), 7.10 (ddd, J = 7.6, 2.4, 1.3 Hz, 1H). 13 N-(4-Cyano-2-nitrophenyl)benzamide (3g).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…13 N-(3-Cyano-5-fluorophenyl)benzamide (3e). 25 Yellow solid (35 mg, 73%); mp 145−146 °C; R f = 0.44 (petroleum ether/ethyl acetate = 4:1); 1 H NMR (400 MHz, CDCl 3 ): δ = 8.37 (s, 1H), 7.93−7.82 (m, 3H), 7.70 (s, 1H), 7.61−7.54 (m, 1H), 7.47 (dd, J = 10.5, 4.7 Hz, 2H), 7.10 (ddd, J = 7.6, 2.4, 1.3 Hz, 1H). 13 N-(4-Cyano-2-nitrophenyl)benzamide (3g).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…General procedure A was followed starting with 7-(methylsulfonyl)-5-fluoro-2-methyl-1 H -indole, which was prepared from 4-fluoro-2-(methylsulfonyl)aniline according to Scheme . , Y = Me. Solid (overall yield, 24%).…”
Section: Methodsmentioning
confidence: 99%
“…Scheme a was followed starting with 5,7-difluoro-2-methyl-1 H -indole, which was prepared from 2,4-difluoroaniline according to Scheme . , Solid (overall yield, 48%). 1 H NMR (400 MHz, MeOD) δ ppm 2.22 (s, 3 H), 3.86 (s, 2 H), 4.84 (s, 2 H), 5.24 (s, 2 H), 6.49–6.56 (m, 1 H), 6.70–6.86 (m, 3 H), 6.74 (d, J = 9.60 Hz, 1 H), 7.11 (d, J = 9.60 Hz, 1 H), 7.18–7.26 (m, 1H).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently reported that nanocrystalline ZnO (Lakshmi Kantam et al, 2005) (Crosignani et al, 2011;Jin et al, 2008) and nano CuO (Yapuri et al, 2013) were used in the synthesis of tetrazole compounds as various homogeneous and heterogeneous catalysts. In addition, metalmodified montmorillonites and zeolite were widely reported, and many metals such as Cu, Mn, Fe, Mo, Al and Co (Clark et al, 1997;Varma, 2002;Carriazo et al, 2003;Shinde et al, 2004;Yin & Shi, 2005;Ben Achma et al, 2008;Rama et al, 2011) were commonly used in improving the catalytic abilities of montmorillonites.…”
Section: Introductionmentioning
confidence: 99%